THE EFFECT OF DRILL AND BOX JUMP EXERCISES ON LEG POWER IN SMASH BACK ATTACK VOLEYBALL - Sufahman, M.; Dos Santos, Maria Herlinda; Rijaluddin, Khalid; Ilahi, Rahmat; Fachrezzy, Fahmy (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
The aim is to determine the effect of drill and box jump training methods on leg power in the smash back attack in men's volleyball. Experimental research uses a quantitative approach, sample of 20 people and data collection through observation, interviews and test instruments. Results (1) significant effect of drill training on leg power in the smash back attack, Pretest results for the Drill training method were 152 and the Posttest were 201 with a difference of 55, while the Pretest for the Box Jump training method was 153 and the Posttest was 175 with a difference. 30, the calculated t value is 3.665> t table 2.145 and the significant value is 0.005 < 0.05 with a time difference of 4.90 seconds. (2) significant effect of box jump training on leg power in the smash back attack as shown by the calculated t value of 2.703> t table 2.145 and a significant value of 0.024 <0.05 with a time difference of 2.20 seconds. (3) box jump training is more effective than drill training on leg power in the smash back attack as shown by the calculated t value of 2.257> t table 2.048 and a significant value of 0.037 < 0.05 with a time difference of 2.60 seconds.